2018
DOI: 10.1159/000487307
|View full text |Cite
|
Sign up to set email alerts
|

Completeness and Legibility of Handwritten Prescriptions in Sana’a, Yemen

Abstract: Objective: The aim of this study was to investigate the completeness and legibility of prescriptions dispensed in community pharmacies located in Sana’a, Yemen. Materials and Methods: A cross-sectional study was conducted at 23 randomly selected community pharmacies throughout the capital city of Sana’a, Yemen, from May 2015 to January 2016. A total of 2,178 prescriptions were analyzed for the essential elements of a complete prescription using a validated checklist. Results: Of the 2,178 prescriptions, 19 (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…There are 37 articles that discuss the incidence of MEs and their factors in Asia, where the articles consist of 9 articles from Southeast Asia [10][11][12][13][14][15][16][17][18] ; 3 articles from East Asia [19][20][21] ; 7 articles from South Asia [22][23][24][25][26][27][28] and 18 articles from West Asia [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . A total of 2 articles discuss the incidence of MEs and their factors in Australia [47][48] .…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…There are 37 articles that discuss the incidence of MEs and their factors in Asia, where the articles consist of 9 articles from Southeast Asia [10][11][12][13][14][15][16][17][18] ; 3 articles from East Asia [19][20][21] ; 7 articles from South Asia [22][23][24][25][26][27][28] and 18 articles from West Asia [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . A total of 2 articles discuss the incidence of MEs and their factors in Australia [47][48] .…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In a similar study conducted at a hospital pharmacy in Asir, Saudi Arabia, the name of patients was missing in 5.4%, prescribers name in 16.7%, and signature in 18.1% of the issued prescriptions (Irshaid et al, 2005). Compared with other international studies, a study in Yemen reported that 99.12% of prescriptions filled at community pharmacies were of poor handwriting (Al-Worafi et al, 2018). However, another study conducted in Riyadh using electronic prescription reported a zero (0.0%) of missing information patients' prescriptions (Albarrak et al, 2014).…”
Section: Fig 3: Categories Of Prescription Errors (Type D)mentioning
confidence: 86%
“…Several preventive measures to reduce prescription errors have been recommended in the past. These included improving communication between pharmacists and physicians, implementation of e-prescriptions, and writing prescriptions in plain English language and names of drugs in generic names (Al-Worafi et al, 2018;Wang et al, 2007). Hospital pharmacists have been shown to play an integral part in reducing prescription errors by reviewing prescriptions prior to dispensing, (Wang et al, 2007) and these have been shown to reduce adverse drug events associated with prescription errors (Lourenco et al, 2016).…”
Section: Fig 3: Categories Of Prescription Errors (Type D)mentioning
confidence: 99%
“…10 Studies examining completeness and legibility of handwritten prescriptions in Sana'a, Yemen indicated that the quality and completeness of prescriptions was found to be very poor. 11 Likewise, a study conducted in Asmara, Eritrea, found the overall completeness of prescriptions to be 78.63%. 12 A study conducted at Tikur Anbesa Specialized Hospital, Addis Ababa, Ethiopia indicated that about 25% of prescribing encounters had patient information such as age and sex and less than 10% of the prescription contained dosage forms as a part of the medication regimen.…”
Section: Introductionmentioning
confidence: 98%
“…This also highlights the need for introducing computerized prescription order entries into general practice. 11 Interventions such as effective communication among health-care providers, implementation of electronic prescription systems, physician education on prescription and pharmacists' involvement in the prescription process should be implemented to improve medication use. 10,32…”
mentioning
confidence: 99%